Measurement of Cellular Immune Response to Viral Infection and Vaccination - Bouwman, Wilbert; Verhaegh, Wim; Holtzer, Laurent; van de Stolpe, Anja (Frontiers in Immunology, 2020)
Combined cellular and humoral host immune response determine the clinical course of a viral infection and effectiveness of vaccination, however the cellular immune response currently cannot be measured on simple blood samples. Functional activity of immune cells is determined by coordinated activity of signaling pathways. mRNA-based JAK-STAT signaling pathway activity assays were developed to quantitatively measure the cellular immune response on Affymetrix data of various types of blood samples from virally infected patients (influenza, RSV, dengue, yellow fever, rotavirus) or vaccinated individuals, and to determine vaccine immunogenicity. JAK-STAT1/2 pathway activity was increased in blood samples of patients with viral, but not bacterial, infection and was higher in influenza compared to RSV-infected patients reflecting known differences in immunogenicity. High JAK-STAT3 pathway activity was associated with more severe RSV infection. In contrast to inactivated influenza virus vaccine, live yellow fever vaccine did induce JAK-STAT1/2 pathway activity in blood samples indicating superior immunogenicity. Normal (healthy) JAK-STAT1/2 pathway activity was established, enabling assay interpretation without the need for a reference sample. The JAK-STAT pathway assays enable measurement of cellular immune response for prognosis, therapy stratification, and vaccine development and clinical testing. A qPCR-based assay is in development, enabling rapid time-to-result in routine hospital labs.